(3TQM GdNeSeGFI GdBjI GdcQjeI ef BjGJ GdCMcGe GdeSJNQL ef GdKeQGJs - (3YHO Gddg Hf eMeO Hf CHj GdbGSe GdRjOj GdYHSj GdfLQj, GdfLQj,J (B877 (3g` s ((3CMeO Hf MSjf Hf eMeO Hf GdgGOi Hf CejQ GdeDefjf jMji Hf MeRI s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf, hUdi Gddg Ydi SjOfG eMeO hBdg ShQI GdHbQI (B((3Ef GdPjf caQhG ShGA Ydjge nCCfPQJge GdBjI s
(3BNQgG (B:s
(3Je GdcJGH Hef Gddg GdYRjR GdhgGH, adg GdMeO cKjQG HcQI hCUjdG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdBjGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs